Editorial: From Social Justice to Educational Justice: Challenging Practice, and Finding Hope - Fulford, Amanda; Victoria Jamieson; Duckworth, Vicky (PRISM: Casting New Light on Learning, Theory and Practice, 2023)
The purpose of this Special Issue is to explore, expose and energise issues around the concepts of social justice and education. We recognise that the notion of ‘social justice’ is not static, and is not shaped in a vacuum; it is iterative by nature, and flows across generations and contexts. The multiple historical and ideological perspectives that arise from this flow include education theory, research, and practice. These positionings offer deep insights into the purpose of education; they also raise important questions: are the social and ideological dynamics a force for challenging the status quo, and for rupturing cycles of inequity or perpetuating inequality? Do they interrupt the relations of dominance and subordination?